Enhanced Geothermal Systems – Promises and Challenges - Anirbid Sircar; Krishna Solanki; Namrata Bist; Kriti Yadav (Center of Biomass & Renewable Energy, Diponegoro University, 2022)
Geothermal energy plays a very important role in the energy basket of the world. However, understanding the geothermal hotspots and exploiting the same from deep reservoirs, by using advanced drilling technologies, is a key challenge. This study focuses on reservoirs at a depth greater than 3 km and temperatures more than 150°C. These resources are qualified as Enhanced Geothermal System (EGS). Artificially induced technologies are employed to enhance the reservoir permeability and fluid saturation. The present study concentrates on EGS resources, their types, technologies employed to extract energy and their applications in improving power generation. Studies on fracture stimulation using hydraulic fracturing and hydro shearing are also evaluated. The associated micro-seismic events and control measures for the same are discussed in this study. Various simulators for reservoir characterization and description are also analyzed and presented. Controlled fluid injection and super critical CO2 as heat transmission fluid are described for the benefit of the readers. The advantages of using CO2 over water and its role in reducing the carbon footprint are brought out in this paper for further studies.